Correlation between hypoxia inducible factor -1α and renin expression in rats kidney induced by cobalt chloride (Medical Journal of Indonesia, 2012)
Background: Cobalt chloride can be used as an agent to stabilize hypoxia inducible factor-1α (HIF-1α) and to imitate hypoxia without low levels of oxygen inside the body. We intended to investigate if there was any regulation of renin expression by HIF-1α. Therefore, we conducted several studies to clarify this possibility starting with the induction of hypoxic mimicry in rats by intra-peritoneal (IP) injection of cobalt chloride (CoCl2) to obtain the levels and pattern of HIF-1α and renin mRNA and protein expression. Methods: Twenty-four rats were randomly divided into four groups, control group and incubation groups 2, 8, and 24 hours after intra-peritoneal injection of 30 mg CoCl2 per kg BW. After the rats were sacrificed, kidneys were excised, weighed and kidney weight compared to BW. Tissue parameters were measured such as RNA concentration, HIF-1α protein by ELISA, and renin mRNA by RT-PCR. Results: Differences between the groups in the ratios of kidney weight to BW and in the concentrations of HIF-1α protein were statistically not significant (p > 0.05). Relative expression of renin mRNA increased markedly starting 8 hours after CoCl2 IP injection (30 times over controls) and further rising until 24 hours (2465 times over controls). Correlation between HIF-1α and renin mRNA by Pearson analysis was strongly positive, but not significant (R = 0.91; p = 0.09). Conclusion: Renin gene regulation in renal hypoxic mimicry strongly correlates withHIF-1α. (Med J Indones. 2012;21:128-32)